Energy methods in structural mechanics a comprehensive introduction to matrix and finite element methods of analysis - Guarracino, F. (Thomas Telford, 1999)
An introduction to the principles underlying finite elements and the computer based methods of the analysis of structures commonly used in industry is provided in this title.